Comparison of Routine Fixation of Tissues with Rapid Tissue Fixation - Tripathi, Meenakshi (JCDR Research and Publications (P) Limited, 2013)
Introduction: Conventional formalin-fixed, paraffin-embedded tissue provides superior cellular morphology and long-term storage. Problems with formalin fixation comprise delay of fixation and variations in the duration of fixation. Microwave assisted tissue fixation removes the use of noxious and potentially toxic formalin that decreases the turnaround time and creates a personnel friendly workflow. Material and Methods: The present study was conducted over a period of two years. One hundred and forty paired tissue sections were taken including both neoplastic and non-neoplastic tissues. One of the paired tissues was fixed in formalin and the other was fixed by using microwave irradiation in phosphate buffered saline. Both were then processed by conventional method. Each slide was examined and rated for the adequacy of fixation by two pathologists in a blinded fashion using 7 parameters: Cellular outline, cytoplasmic detail, nuclear detail, erythrocyte integrity, lymphocyte appearance, overall morphology and overall staining. Results: Statistical analysis showed that sections obtained from microwave fixed tissues were comparable to that of routinely fixed tissue. The p-values of all parameters were not significant except for the overall morphology for which p-value was significant owing to loss of tissue in some cases. Conclusion: Microwave irradiation substantially shortened the time from specimen reception to diagnosis (turnaround time) and allowed same-day tissue processing and diagnosis of specimens without compromising the overall quality of the histologic section.